The Effectiveness of Educational-Based Wordwall Media on Students’ Collaboration Skills in Social Studies Learning - Husril Kadir; Nuraedah Nuraedah; Ika Listiqowati; Widyastuti Widyastuti; Sunarto Amus; Hasdin Hanis (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The development of 21st-century education requires students to possess not only academic competencies but also collaborative skills, which have become essential in the learning process. However, preliminary observations at SMP Negeri 23 Sigi revealed that eighth-grade students' collaboration skills in Social Studies learning were still relatively low. This condition was indicated by limited student participation in group discussions, minimal interaction among students, and the suboptimal use of learning media that could encourage active engagement. Therefore, technology-based learning media such as Wordwall are considered a promising alternative for creating a more interactive, engaging, and collaborative learning environment. This study aimed to analyze the effectiveness of education-based Wordwall media in improving eighth-grade students’ collaboration skills in Social Studies learning at SMP Negeri 23 Sigi, to examine students’ collaboration skills during the learning process, and to describe the integration of Wordwall media into Social Studies instruction. The study employed a descriptive qualitative approach with data collected through observations, interviews, and documentation. The research participants consisted of Social Studies teachers and eighth-grade students at SMP Negeri 23 Sigi. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that the use of educational-based Wordwall media was effective in enhancing students’ collaboration skills. Students became more actively involved in discussions, demonstrated productive teamwork, respected their peers’ opinions, shared responsibilities, and showed improvements in communication and group decision-making skills. Furthermore, the integration of Wordwall created a more enjoyable and interactive learning environment, encouraging optimal student engagement in Social Studies. The implications of this study suggest that Wordwall can serve as an effective digital learning medium to support the development of students’ collaboration skills and improve the quality of Social Studies instruction in schools.